Polychlorinated dibenzo-p-dioxins, dibenzofurans and polychlorinated biphenyls in New Zealand cetaceans - Jones, Paul D.; Hannah, Donald J.; Buckland, Simon J.; Van Maanen, Tania; V. Lea Ihem, Scott; Dawson, Stephen; Slooten, Elisabeth; Van Helden, Anton; Donoghue, Michael (J. Cetacean Res. Manage., 1999)
Limited information is available on the concentrations of halogenated aromatic hydrocarbons (HAHs) in cetaceans from the Southern Hemisphere. This paper presents data on blubber concentrations of polychlorinated dibenzo-p-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs) and polychlorinated biphenyls (PCBs) in Hector's dolphins, dusky dolphins, southern right whale dolphins, blue whales, minke whales, Gray's beaked whales, Cuvier's beaked whales and pygmy right whales stranded in New Zealand. Both HAH concentrations and toxic equivalents (TEQs) are found to be higher in Hector's dolphins, a species with an inshore distribution, than in other odontocetes, which are more oceanic. Baleen whales, which are oceanic and feed at lower trophic levels, present the lowest levels of pollutants, with PCDD and PCDF concentrations usually below detection limits. The PCB profiles of the various species suggest that they are exposed to different PCB sources. Overall, HAH levels detected are lower than those reported for comparable species in the Northern Hemisphere. The relative abundance of low chlorinated PCB congeners in New Zealand cetaceans, as compared to those from northern waters, suggests that the origin of these compounds is mostly atmospheric deposition.